Brain disease, connectivity, plasticity and cognitive therapy: A neurological view of mental disorders - G. Lubrini; A. Martín-Montes; O. Díez-Ascaso; E. Díez-Tejedor (Neurología (English Edition), 2018)
Introduction: Our conception of the mind-brain relationship has evolved from the traditional idea of dualism to current evidence that mental functions result from brain activity. This paradigm shift, combined with recent advances in neuroimaging, has led to a novel definition of brain functioning in terms of structural and functional connectivity. The purpose of this literature review is to describe the relationship between connectivity, brain lesions, cerebral plasticity, and functional recovery. Development: Assuming that brain function results from the organisation of the entire brain in networks, brain dysfunction would be a consequence of altered brain network connectivity. According to this approach, cognitive and behavioural impairment following brain damage result from disrupted functional organisation of brain networks. However, the dynamic and versatile nature of these circuits makes recovering brain function possible. Cerebral plasticity allows for functional reorganisation leading to recovery, whether spontaneous or resulting from cognitive therapy, after brain disease. Conclusions: Current knowledge of brain connectivity and cerebral plasticity provides new insights into normal brain functioning, the mechanisms of brain damage, and functional recovery, which in turn serve as the foundations of cognitive therapy. Resumen: Introducción: La relación entre mente y cerebro ha evolucionado desde el clásico dualismo hasta los conocimientos actuales que ponen de manifiesto que las funciones mentales son el resultado de la actividad cerebral. Este cambio de paradigma, junto con los recientes avances en diferentes técnicas de neuroimagen, ha dado lugar a una novedosa concepción del funcionamiento cerebral en términos de conectividad estructural y funcional. El objetivo del presente trabajo es describir la relación entre conectividad, lesión cerebral, plasticidad cerebral y recuperación funcional. Desarrollo: Si la función cerebral surge de la organización en red del cerebro como un todo, la disfunción cerebral se puede producir por una alteración en la conexión de estas redes. Así, a partir del modelo conectivista, los trastornos cognitivos y del comportamiento que aparecen tras una afección cerebral se describen como consecuencia de una alteración en la organización funcional de las redes cerebrales. Sin embargo, la pérdida de funciones puede ser recuperada gracias a la capacidad de los circuitos de ser dinámicos y versátiles. La plasticidad cerebral permite una reorganización funcional que llevará a una recuperación, espontánea o potenciada con terapia cognitiva, después de algún tipo de enfermedad cerebral. Conclusiones: El conocimiento de la conectividad y la plasticidad cerebrales proporciona una nueva perspectiva desde la que entender el funcionamiento cerebral en condiciones normales, los mecanismos del daño cerebral y los de la recuperación funcional, constituyendo las bases para el desarrollo de la terapia cognitiva. Keywords: Brain plasticity, Brain damage, Cognitive therapy, Behaviour disorders, Mental disorders, Palabras clave: Plasticidad cerebral, Daño cerebral, Terapia cognitiva, Alteraciones del comportamiento, Trastornos mentales